Innovative canting: A triz approach to improve traditional batik production process in small and medium enterprise - Taufiq Immawan; Fauzan Mahardika Pratama; Muhammad Iqbal Rofif; Farid Agung Waskita; Meilinda Fitriani Nur Maghfiroh (Universitas Serang Raya, 2025)
This research aims to improve the efficiency of the canting tool used in the Batik-making process in Giriloyo Village. One of the main issues identified is the suboptimal size of the canting spout, which causes wax blockages due to dirt particles. This study employs TRIZ tools, including Function Analysis, to identify problems, develop innovative solutions to the issues, and develop solutions that address contradictions in the canting system. The analysis results indicate that several inventive principles, such as Merging, Beforehand Cushioning, Segmentation, and Feedback, can enhance the canting tool's performance. Proposed solutions include adding a heater, filter, flow regulator, and interchangeable canting spouts to meet different needs. These solutions can accelerate the Batik-making process, reduce production costs, and enhance market competitiveness. However, further verification is required to validate the proposed design's superiority over traditional canting tools. This research opens opportunities for further development in Batik tool innovations to enhance the sustainability of the Batik creative industry in Indonesia.